EFFECT OF TYPE OF FREEZING ON THE FUNCTIONAL CHARACTERISTICS OF FROZEN THAWED BULL SPERMATOZOA - NAGENDRAKUMAR, S B; KATHIRESAN, D (The Indian Journal of Animal Reproduction, 2023)
Programmable biological freezers can be used to control and optimize the freezing rate forsuccessful cryopreservation of bull spermatozoa. The effect of freezing methods on the functionalcharacteristics of frozen thawed bull spermatozoa was studied. Semen samples collected from Jerseycross (n=6) and Friesian cross (n=6) bulls were extended in Tris egg citric acid diluent. The sampleswere split and cryopreserved using static vapor freezing and programmed freezing. In both the methodsof cryopreservation the post-thaw semen showed a highly significant (P
Keywords: Bull; Cryopreservation; Programmed freezing; Static vapour freezing